2014
DOI: 10.4028/www.scientific.net/msf.803.63
|View full text |Cite
|
Sign up to set email alerts
|

Light Weight Geopolymer Paste Made with Sidoarjo Mud (Lusi)

Abstract: This paper presents the efforts of how to use the solid form of Sidoarjo mud as a base material of lightweight-geopolymer paste. The mud, which is called Lusi was mixed with a class F fly ash. Some experimental results have shown that mixing mud with fly ash and alkali was potential to become a binder in concrete, instead of Portland cement. Alkaline solutions used in the mixture were NaOH of 12 M and 14 M and Na2SiO3combined in the ratio of 1:2.5 by weight. Aluminum powder was applied as a foaming agent. It s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The pH value was tested by dissolving fly ash into distilled water followed with pH measurement. Fly ash with pH value ranged from 8 to 11 tends to experience rapid setting [14]. In addition, pH value of fly ash has closely correlation with its CaO content.…”
Section: Ph Testmentioning
confidence: 94%
See 2 more Smart Citations
“…The pH value was tested by dissolving fly ash into distilled water followed with pH measurement. Fly ash with pH value ranged from 8 to 11 tends to experience rapid setting [14]. In addition, pH value of fly ash has closely correlation with its CaO content.…”
Section: Ph Testmentioning
confidence: 94%
“…[13] The research conducted by Tajunnisa stated that more irregular shape particles required more water in mixing geopolymer paste [8].With the purpose of produce geopolymer paste, water content is represented by alkali solution. It is also concluded that concentration and composition of alkali solution plays an important role in developing mechanical properties of geopolymer paste [20][21][22].…”
Section: Sem Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have confirmed that steam curing at a temperature range of 60 o C-80 o C contributes to faster strength development at early age [9] and promotes the reaction of geopolymerization [10,11]. On the other hand, some studies have suggested that moist curing is more recommended than wet curing [12].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of geopolymer concrete raw materials derived from coal combustion waste (fly ash). Utilization of industrial waste material and non industry are the other reason why geopolymer concrete worth the continued research [3][4][5][6][7][8][9][10] to support environmental researches.…”
Section: Introductionmentioning
confidence: 99%